1985
DOI: 10.1002/aic.690310914
|View full text |Cite
|
Sign up to set email alerts
|

Tracer diffusion of aromatic hydrocarbons in liquid cyclohexane up to its critical temperature

Abstract: Tracer diffusion coefficients in liquid cyclohexane of benzene, toluene, p-xylene, mesitylene, naphthalene, and phenanthrene have been determined from 298.2 to 523.2 K ( TR = 0.54 -0.95) using the Taylor dispersion method. Positive deviations proached, but a rough-hard-sphere theory is found to be adequate for describing the data across the entire temperature range. On the basis of the computer simulation results for hard-sphere fluids, correlations involving solute and solvent critical volumes and their molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 14 publications
(12 reference statements)
1
20
1
Order By: Relevance
“…15, as a simplification of Eq. 11, to be valid for binary diffusion coefficients (Sun and Chen, 1985a,b, 1986 , 1987a,b;Erkey et al, 1990;Funazukuri et al, 1991;Liong et al, 1991). Figure 2 shows plots of D,,/dT vs. C02 free volume [u, -( u~)~] for naphthalene, measured by Feist and Schneider (1982), Lauer et al (1983), Sassiat et al (1987), and Funazukuri et al (1989), together with those of D2,/dT for CO, self-diffusion data ( O'Hern and Martin, 1955;Takahashi and Iwasaki, 1966;Robinson and Stewart, 1968).…”
Section: *Imentioning
confidence: 97%
“…15, as a simplification of Eq. 11, to be valid for binary diffusion coefficients (Sun and Chen, 1985a,b, 1986 , 1987a,b;Erkey et al, 1990;Funazukuri et al, 1991;Liong et al, 1991). Figure 2 shows plots of D,,/dT vs. C02 free volume [u, -( u~)~] for naphthalene, measured by Feist and Schneider (1982), Lauer et al (1983), Sassiat et al (1987), and Funazukuri et al (1989), together with those of D2,/dT for CO, self-diffusion data ( O'Hern and Martin, 1955;Takahashi and Iwasaki, 1966;Robinson and Stewart, 1968).…”
Section: *Imentioning
confidence: 97%
“…This requires data from diffusion experiments with a solute having a known value of Db For this reason, anthracene was chosen because it has a relatively large molecule size, is easily analyzed, and has a known value of D b The resulting effective diffusivities for anthracene in cyclohexane solvent with the three catalysts, as shown in Table VI, together with a measured Db of 1.2 X 10" cm2/s (Sun and Chen, 1985) yielded from eq 9 a T of 1.37. By applying the same T to the other solutes, values of Db were obtained (Table IV), which are within 10% of the calculated values from eq 7.…”
Section: Restrictive Diffusion Correlationsmentioning
confidence: 99%
“…The above experimental results are in agreement with the MCT study of Bhattacharyya and Bagchi,25(b) which found that the effect of solute mass on diffusion is generally quite weak; in particular, the solute-mass dependence can normally be considered as negligibly small when changes of solute mass are small within a factor of 2 or so. It should be pointed out that it 51,53,54 have reported tracer diffusivities of nonassociated aromatic solutes in cyclohexane, ethanol, and n-hexane at temperatures above 298.2 K. We have carried out linear regressions for their data at temperatures below the normal boiling point of solvent (but excluding those data at higher temperatures which were measured at different pressures above 1 atm). All data, except one of Dymond's 14 In view of the correlation coefficients and the average % deviations for the 13 sets of linear regressions in Table II, it is clear that Eq.…”
Section: A Solute Dependencementioning
confidence: 99%
“…Free volume theory, which has affinity with the kinetic theory, has received considerable attention in the past few decades, and there are many reports on the successful use of that theory for the study of diffusion in the literature. 51,61,[91][92][93][94][95][96] There are different approaches of using the free volume theory, and the simplest is probably the one given by Hildebrand. 91 Based on Batschinski's equation 97 for viscosity, Hiddebrand suggested for self diffusivity D s the following:…”
Section: B Solvent Dependencementioning
confidence: 99%